2003
DOI: 10.1007/s00125-003-1193-6
|View full text |Cite
|
Sign up to set email alerts
|

Leptin as an adjunct of insulin therapy in insulin-deficient diabetes

Abstract: Aims/hypothesis. The purpose of this study was to assess the therapeutic implication of leptin in insulindeficient diabetes. Methods. Insulin-deficient diabetes was induced by streptozotocin (STZ) in transgenic skinny mice overexpressing leptin. Plasma concentrations of glucose, insulin, and leptin were measured. The effects on body weight, food intake, and hypothalamic gene expressions were analyzed. After diabetes was induced, graded doses of insulin ranging from 0.4 to 51.2 mU·g -1 ·day -1 were injected. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 38 publications
2
39
0
2
Order By: Relevance
“…Recently, we and others confirmed that leptin treatment effectively reduces food intake and improves hyperglycaemia, hypertriacylglycerolaemia and fatty liver in patients with lipoatrophic diabetes [13][14][15][16]. In addition, we demonstrated that leptin is useful as a glucose-lowering agent in a mouse model of insulin-deficient diabetes induced by high-dose streptozotocin (STZ) [11]. Leptin infusion reduced the dose of insulin required to improve hyperglycaemia by more than 90%, and prevented insulin-induced body weight gain in STZ-injected mice.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Recently, we and others confirmed that leptin treatment effectively reduces food intake and improves hyperglycaemia, hypertriacylglycerolaemia and fatty liver in patients with lipoatrophic diabetes [13][14][15][16]. In addition, we demonstrated that leptin is useful as a glucose-lowering agent in a mouse model of insulin-deficient diabetes induced by high-dose streptozotocin (STZ) [11]. Leptin infusion reduced the dose of insulin required to improve hyperglycaemia by more than 90%, and prevented insulin-induced body weight gain in STZ-injected mice.…”
Section: Introductionmentioning
confidence: 81%
“…We previously generated transgenic skinny mice (LepTg) overexpressing leptin under the control of the liver-specific human serum amyloid P component promoter [6]. LepTg mice showed elevated plasma leptin levels comparable to those of obese human individuals, providing a unique experimental model to investigate various actions of leptin [6][7][8][9][10][11]. LepTg mice exhibited increased glucose metabolism and insulin sensitivity with augmented liver and skeletal muscle insulin receptor signalling [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plusieurs études chez des rongeurs insulinodéficients ont suggéré que l'administration de leptine pourrait traiter le diabète ou améliorer l'effet de l'insuline [14][15][16][17]. La première étude, publiée en 1999 [15], a pris pour modèle des rats traités par la streptozotocine, et a montré que l'infusion sous-cutanée de leptine, en l'absence d'insulinothéra-pie, pouvait normaliser les glycémies.…”
Section: Amélioration Par La Leptine Des Effets De L'insulineunclassified
“…De plus, la leptine restaurait également, dans ce modèle, la sensibilité hépatique et périphéri-que à l'insuline évaluée par le clamp Les animaux contrôles nourris de la même façon que ceux traités par la leptine perdaient du poids sans normaliser leur glycémie, montrant que la diminution de la prise alimentaire n'explique pas, à elle seule, l'effet de la leptine sur la normalisation glycémique chez les rongeurs insulinodéficients. En 2003, Miyanaga et al [16] ont montré, chez des souris rendues diabétiques après destruction des îlots bêta par la streptozotocine, que l'augmentation des concentrations circulantes de leptine, obtenue par transgenèse (surexpression du gène ob chez les « skinny mice ») ou par administration de leptine exogène par voie sous-cutanée, permettait de réduire significativement les besoins en insuline nécessaires à la normalisation des glycémies. Comme dans l'étude précédente, le rôle adjuvant de la leptine sur l'insulinothérapie n'était pas uniquement lié à son effet anorexigène, puisque l'hyperglycémie n'était pas diminuée par le contrôle identique 2 Le clamp euglycémique hyperinsulinémique consiste à perfuser de fortes doses d'insuline à débit constant tout en maintenant la normoglycémie grâce à une perfusion de glucose à débit variable.…”
Section: Amélioration Par La Leptine Des Effets De L'insulineunclassified